LEGAL AUTHENTICATION FOR DISPOSITIONS OF RETURN IN THE DONATION - مصطفى هاشمي (Tamanrasset University Center, 2021)
The law generally provided stipulated the revocation of the donation, and made an exception under section 211 of the Family Code, allowing parents to revoke the donation for their child under certain conditions. Since the texts of family law are ascribed to the noble Shari'a, the research seeks to reveal the material sources of this question and to determine the standard followed for taking them, especially since the revocation provisions in the donation are detailed and complete for various cases in Islamic fikhs. legislation, unlike family law, which was limited to the development of two sections dealing with revocation.